Gothic Presences in Eating your heart out, a Collaborative Sculpture of Rui Chafes and Vera Mantero - Lima, Maria Antónia (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
Eating your heart out, an installation that represented Portugal at the 26th São Paulo Biennial, has a metaphoric title that expresses the savagery of a negative desire which surpasses all the civilized limits to express the difficult presence of a body through some relational forms created by sculptor Rui Chafes and dancer/choreographer Vera Mantero. The relations between an iron sculpture and a living body produce a tension between the absolute closure of Chafes’s sculpture and the infinite movement of Mantero’s choreographies. The duplicity of this relation, which combines repression and freedom, limitation and transcendence, conformity and subversion, savagery and poetry, violence and beauty, originates an endless dialectic confrontation that leads to many contradictory possibilities, which increase the difficulties to solve the enigma of the encounter of these two Portuguese artists. Its mystery and strangeness can be understood through the presence of certain paradoxes of gothic sublimity present in works so determined by the condition of unrepresentability. This condition developed in Chafes and Mantero a fascination with the negative pleasures of an art that creates secrets instead of their resolution and that produces exhaustion and disquiet instead of order and stability. Consequently, their works can be very close to a gothic aesthetics usually interested in primitive emotions and mysteries that have the power to disturb and resist reason like a dancer’s naked body full of arborescent motifs on her skin, in a suspended iron chair 5 metres above the ground.